Шёл по городу волшебник: повесть, в которой случаются чудеса / Юрий Томин - Томин Юрий Геннадьевич (Знание, 1993)
Экземпляры: ф. 2 (20181019) / Инвентарный номер: 109002 / Цена: 10.00 / Авт.знак: Т 56 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6